Observation of the narrow state X(3872) → J/ψπ+π- in p̄p collisions at √s = 1.96 TeV - Acosta, D; Affolder, T; Ahn, M; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2004)
The observation of a state consistent with X(3872) decaying into J/ψπ+π- was reported. The X(3872) mass was measured to be 3871.3±0.7(stat)±0.4(syst)MeV/c2 from a sample of 730±90 candidates. The observed width was consistent with the detector resolution. The results were found to be converging well with the measurements by the Belle Collaboration using b± decays.